PENGARUH PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII SMP IT BUDI LUHUR CIMAHI PADA MATERI PERSAMAAN GARIS LURUS - Amalia Yuliani; Euis Eti Rohaeti; Ratna Sariningsih; M. Afrilianto (IKIP Siliwangi, 2023)
The purpose of this study is to analyze and find out the mathematical communication skills of junior high school students by using a scientific approach to the material of straight-line equations. This research consists of two cycles based on the Kemmis & Taggart model. which consists of: planning, implementation, observation, and reflection. The subject of this study was 30 students of VIII grade from SMP IT Budi Luhur Cimahi of 2021/2022 academic year. The test instrument used in accordance with the indicators of mathematical communication ability is in the form of a description of as many as 5 numbers. Normalized gain data was generated in this study, resulting in a score of 0.36. Data processing in the study was obtained from normalized gain data, with a score of 0.36. This shows that students' mathematical communication skills have improved, with a moderate category. The non-test instruments used included a questionnaire on the scale of learning interest attitudes as many as 16 balanced statements with positive and negative responses. The results of the response to students' interest in learning mathematics have a positive effect on students' mathematical communication, namely 76.6 with a positive category.